2020
DOI: 10.31224/osf.io/fhqd7
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Real-time measurement of tumour hypoxia using an implantable microfabricated oxygen sensor

Abstract: Hypoxia commonly occurs within tumours and is a major cause of radiotherapy resistance. Clinical outcomes could be improved by locating and selectively increasing the dose delivered to hypoxic regions. Here we describe a miniature implantable sensor for real-time monitoring of tissue oxygenation that could enable this novel treatment approach to be implemented. The sensor uses a solid-state electrochemical cell that was microfabricated at wafer level on a silicon substrate, and includes an integrated reference… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 64 publications
0
6
0
Order By: Relevance
“…Silicon sensors with platinum IDEs were fabricated as previously described. [12] This created platinum interdigitated electrodes on a silicon substrate covering a 2,500 µm 2 area. A Perspex chamber was attached over each sensor, sterilised with 70% ethanol and rinsed thrice with de-ionised water before cell seeding and impedance measurements made.…”
Section: A Sensor and Chamber Fabricationmentioning
confidence: 99%
“…Silicon sensors with platinum IDEs were fabricated as previously described. [12] This created platinum interdigitated electrodes on a silicon substrate covering a 2,500 µm 2 area. A Perspex chamber was attached over each sensor, sterilised with 70% ethanol and rinsed thrice with de-ionised water before cell seeding and impedance measurements made.…”
Section: A Sensor and Chamber Fabricationmentioning
confidence: 99%
“…Circulating levels of sIL6R have been found to be elevated (in comparison to healthy individuals) in patients with different cancer types, including myeloma, leukaemia, bladder, prostate and hepatocellular cancer, with higher levels associated with tumour grade, volume or disease spread [152][153][154][155][156][157]. While significantly higher sIL6R levels have also been reported in patients with BC [158,159], it has been suggested that larger sample cohorts need to be assessed before conclusions can be drawn regarding the prognostic potential of sIL6R levels in this cancer type [27].…”
Section: Circulating Il6 Level As a Biomarkermentioning
confidence: 99%
“…STHLM3 is a risk-based model for PC screening that combines 232 SNPs, a combination of plasma protein biomarkers (PSA, iPSA, fPSA, hK2, beta-microseminoprotein and macrophage inhibitory cytokine 1) and clinical variables (family history, age, prostate exam and previous biopsies) [153]. Studies have found that this model performed better than PSA alone for the detection of high-risk PC, exhibiting its potential to improve PC diagnosis by significantly reducing the number of unnecessary biopsies taken, while also preserving the same sensitivity to diagnose clinically significant PC [153][154][155][156][157].…”
Section: The Sthlm3 Modelmentioning
confidence: 99%
“…Many studies have conducted in vivo measurements of oxygen tension ( p o2 ) in tissues, for example, brain, lung and tumor, using techniques such as electrode sensors, 14 optical probes, 15 electron paramagnetic resonance (EPR), 16 and blood oxygenation level dependent (BOLD) 17 . However, real‐time oxygen measurements during FLASH RT are more challenging than these steady‐state studies.…”
Section: Introductionmentioning
confidence: 99%